First Principles Study of Electronic and Optical Properties of Pristine and X (Cu, Ag And Au) Doped BiOBr - Paudel, Samir; Adhikari, Puspa Raj; Upadhyay, Om Prakash; Kaphle, Gopi Chandra; Srivastava, Anurag (Journal of Institute of Science and Technology, 2018)
The electronic structures and optical properties of pristine BiOBr and Cu, Ag and Au doped BiOBr have been analyzed by using a standard density functional theory based ab-initio approach employing generalized gradient approximation through revised Perdew Burke Ernzerhoff type parameterization. The calculation shows that both the doped and pristine BiOBr have indirect band gap, the band gap of the pristine BiOBr found 2.22eV, whereas band gap significantly reduced after doping Cu, Ag and Au on BiOBr. The band gap of Cu, Ag and Au doped BiOBr are 1.2eV, 0.9eV and 1.76eV respectively. The optical properties have been studied through dielectric function, both pure and doped BiOBr shows anisotropic nature. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, page: 63-69